2016
DOI: 10.1093/hmg/ddw109
|View full text |Cite
|
Sign up to set email alerts
|

5-Hydroxymethylation-associated epigenetic modifiers of Alzheimer’s disease modulate Tau-induced neurotoxicity

Abstract: Alzheimer's disease (AD) is a chronic neurodegenerative disorder characterized by progressive deterioration of cognitive function. Pathogenesis of AD is incompletely understood; evidence suggests a role for epigenetic regulation, in particular the cytosine modifications 5-methylcytosine and 5-hydroxymethylcytosine (5hmC). 5hmC is enriched in the nervous system and displays neurodevelopment and age-related changes. To determine the role of 5hmC in AD, we performed genome-wide analyses of 5hmC in DNA from prefro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 68 publications
4
40
0
2
Order By: Relevance
“…Advances in loci- specific techniques to study whole epigenomes have increased greatly in the past several years, however the cost of this new technology is high, limiting the number of subjects per analysis. Although samples sizes were small, two previously published studies of differentially hydroxymethylated regions of the AD genome in prefrontal cortex tissue specimens (Bernstein et al 2016, Zhao et al 2017) showed several overlapping genes with altered hydroxymethylation in our gene list. One gene common to all three genome-wide 5-hmC studies in AD brain, myelin transcription factor 1-like ( MYT1L ), was used to produce induced neuronal cells and has been described as a neuronal fate inducing factor (Vierbuchen et al .…”
Section: Discussionmentioning
confidence: 83%
“…Advances in loci- specific techniques to study whole epigenomes have increased greatly in the past several years, however the cost of this new technology is high, limiting the number of subjects per analysis. Although samples sizes were small, two previously published studies of differentially hydroxymethylated regions of the AD genome in prefrontal cortex tissue specimens (Bernstein et al 2016, Zhao et al 2017) showed several overlapping genes with altered hydroxymethylation in our gene list. One gene common to all three genome-wide 5-hmC studies in AD brain, myelin transcription factor 1-like ( MYT1L ), was used to produce induced neuronal cells and has been described as a neuronal fate inducing factor (Vierbuchen et al .…”
Section: Discussionmentioning
confidence: 83%
“…Specifically, 5-methylcytosine (5mC) is recognized as an important regulator of gene expression [14], but is not the only DNA-based epigenetic modification. 5-Hydroxymethylcytosine (5hmC), another equally important epigenetic regulator, is widely distributed in the brain [15] and is implicated in fetal brain development [16] as well as in different brain disorders [17,18]. Disease-specific differences in global 5mC and 5hmC levels have been reported in selected areas of the brain in MSA patients by immunodetection [19].…”
Section: Introductionmentioning
confidence: 99%
“…The recent studies has revealed that the level of 5hmC reduced 10% after ten-eleven-translocation 1 (Tet1) knockdown can retard the proliferation of neural progenitor cells and impair the abilities of spatial learning and memory (Rudenko et al, 2013; Zhang et al, 2013). Moreover, declining 5hmC modulates transcriptional activity of some genes involved in neurogenesis in AD mice, which also indicates that 5hmC closely connects with memory maintenance (Bernstein et al, 2016; Shu et al, 2016). Besides Tet family, Ubiquitin-like with PHD and ring finger domains 2 (Uhrf2) is currently considered as a novel regulator via its SRA domain (Zhou et al, 2014) to maintain 5hmC level and abilities of learning and memory in brain (Chen et al, 2017b).…”
Section: Introductionmentioning
confidence: 88%